A Narrative Synthesis of the Components of and Evidence for Patient- and Family-Centered Care - Gallo, Kaitlin P. (Clin Pediatr (Phila), 2015)
A narrative synthesis was conducted to determine typical patient- and family-centered care (PFCC) components and their link to outcomes in pediatric populations. 68 studies with PFCC interventions and experimental designs were included. Study features were synthesized based on five core PFCC components (i.e., education from the provider to the patient and/or family, information sharing from the family to the provider, social-emotional support, adapting care to match family background, and/or shared decision-making) and four outcome categories (health status; the experience, knowledge, and attitudes of the patient/family; patient/family behavior; or provider behavior). The most common PFCC component was education; the least common was adapting care to family background. The presence of social-emotional support alone, as well as educational interventions augmented with shared decision making, social-emotional support, or adaptations of care based on family background, predicted improvements in families' knowledge, attitudes, and experience. Interventions that targeted the family were associated with positive outcomes.